Work Values, Emotional Intelligence, Work Environment and Career Commitment among Gen Y - Nur Damayanti; Khulida Kirana Yahya; Fee Yean Tan (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
This article reviews the relationship between work values, emotional intelligence, work environment and career commitment in Indonesia banking industry. The future banking industry will be filled by Generation Y or millennial who has different behavior and characteristics of previous generations. Generation Y, known as a generation that is very expressive, confident but does not have a career commitment and is not interested in details and has a different view from the previous generation. Generation Y tends to think that they are able to compare with other companies and there is no emotional connection or loyalty to the company as the previous workforce. If they feel their expectations of career aren't being met, they will switch jobs. A pilot test of 50 respondents at Mandiri bank, Jakarta were surveyed. This finding reports the significant and positive impact of work values, emotional intelligence and work environment on career commitment. The result indicated that career commitment was influenced by work values, emotional intelligence and work environment. The discussion outlines the results of the research while the implications are taken to put forward the theoretical and practical contributions of this research.